Improving teaching in a BSc Animal Science course through interactive classes - Luis Alves Neves, André (Improving University Science Teaching and Learning, 2023)
This pedagogical project reports my experiences implementing interactive classes in a BSc Animal Science course, Dyrs Ernæring og Præstation (DEP), from January to April 2022. The DEP course requires that students present seven consecutive projects consisting of a comparative analysis of feed plans and nutrient metabolism for three animal species (01 ruminant, 01 monogastric, and 01 animal of choice). Although the students work in groups during the project preparation stage, the DEP teachers usually deliver the lectures based on a traditional content-oriented approach (PPT slides, etc.). This means that the teacher does most of the talking, and the students’ attention is almost exclusively on the lecturer. This problem gives the educators an excellent opportunity to engage students with interactive classes to improve participation and create a more collaborative learning environment in the classroom. It is expected that the outcomes of this pedagogical project will have practical applications in the future development of the DEP course.